An Analysys Of Vocabulary Mastery Efects On Students’ Speaking Ability In SMA YPK Pematangsiantar - Indra Jayanti Damanik; Ridwin Purba; Ayuning Tiyas (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
This research explores the relationship between vocabulary mastery and speaking ability among 10th-grade students at SMA YPK Pematangsiantar during the 2022/2023 academic year. The study aims to address the challenges students face in language learning by investigating the impact of vocabulary on speaking skills. The research employs qualitative methodology, utilizing interviews and questionnaires for data collection. The findings reveal that while vocabulary is recognized as essential for communication, many students struggle with mastering it due to complexities, pronunciation difficulties, and concerns about making mistakes. The study concludes that vocabulary plays a crucial role in language acquisition, influencing students' self-confidence and proficiency in speaking English. The research emphasizes the significance of vocabulary in effective communication and highlights the need for improved teaching strategies to enhance students' vocabulary mastery and speaking abilities